Technological Adaptation in Post-School Education: A Systematic Review of Design and Application Trends in Technology-Enhanced Learning Environments - Parwita Setya Wardhani; Seger Handoyo; Fendy Suhariadi (Psikostudia : Jurnal Psikologi, 2026)
The growth in the use of technology with regard to learning in post-school education has shifted focus onto the psychological mechanisms behind engagement and performance of learners. Rather than just focusing on the technology, a systematic literature review which synthesizes 40, peer-reviewed, academic writings on this subject published between 2015 and 2024 examines how new technologies impact key psychological processes. Constructivist learning theory, self-determination theory and social cognitive theory framed the thematic synthesis which led to five major psychological themes. Immersive environments provide support for embodied cognition (cognitive processing through sensory input) and promote a deeper level of conceptualization of the subject(s) studied; Artificial intelligence and learning analytics provide perception of competence and self-regulation through adaptive feedback to learners; Mobile and blended instructional models facilitate autonomy and agency for learners; Intelligent Institute systems provide systemic personalization which facilitates sustained engagement by learners; and Gamification and simulation-based environments foster intrinsic motivation and collaborative efficacy. The findings indicate that tech-enhanced learning environments function as structured psychological ecosystems which affect behavioral, cognitive and social processes, related to motivation, cognitive activation and social interaction. This literature review adds to the field of educational psychology by defining the ways in which digital environments mediate learning through the motivational and cognitive pathways.Pertumbuhan penggunaan teknologi dalam pembelajaran di pendidikan pascasekolah telah menggeser fokus ke mekanisme psikologis di balik keterlibatan dan kinerja peserta didik. Dari pada hanya berfokus pada teknologi, tinjauan literatur sistematis yang mensintesis 40 tulisan akademis yang ditinjau sejawat tentang subjek ini yang diterbitkan antara tahun 2015 dan 2024 meneliti bagaimana teknologi baru memengaruhi proses psikologis utama. Teori pembelajaran konstruktivis, teori penentuan diri, dan teori kognitif sosial menjadi kerangka sintesis tematik yang menghasilkan lima tema psikologis utama. Lingkungan imersif memberikan dukungan untuk kognisi yang terwujud (pemrosesan kognitif melalui masukan sensorik) dan mendorong tingkat konseptualisasi yang lebih dalam tentang subjek yang dipelajari; kecerdasan buatan dan analitik pembelajaran memberikan persepsi kompetensi dan pengaturan diri melalui umpan balik adaptif kepada peserta didik; model pembelajaran seluler dan campuran memfasilitasi otonomi dan agensi bagi peserta didik; sistem Institut Cerdas menyediakan personalisasi sistemik yang memfasilitasi keterlibatan berkelanjutan oleh peserta didik; dan gamifikasi dan lingkungan berbasis simulasi menumbuhkan motivasi intrinsik dan efikasi kolaboratif. Temuan menunjukkan bahwa lingkungan pembelajaran yang didukung teknologi berfungsi sebagai ekosistem psikologis terstruktur yang memengaruhi proses perilaku, kognitif, dan sosial, terkait dengan motivasi, aktivasi kognitif, dan interaksi sosial. Tinjauan literatur ini menambah bidang psikologi pendidikan dengan mendefinisikan cara-cara di mana lingkungan digital memediasi pembelajaran melalui jalur motivasi dan kognitif.